Is Azekah Really the Hometown of Micah the Morasthite?: Some Critical Remarks - Gaß, Erasmus (Zeitschrift für die alttestamentliche Wissenschaft, 2023)
In a recent article, Oded Lipschits and Jakob Wöhrle argue for Tel Azekah as the hometown of the biblical prophet Micah of Moresheth Gath. However, the main arguments are not convincing and can easily be refuted. Above all, the overall rejection of the patristic sources is methodologically questionable and cannot stand up to scrutiny since the alleged contradictoriness does not exist within the Christian topographical tradition. Moreover, it can be shown that geographical, epigraphical, etymological and archaeological data were used in a one-sided and erroneous way.